The Modification Effect of Piston Crown on Four Stroke One Cylinder Diesel Engine using Biodiesel B30 on Noise Based on Simulation. - Beny Cahyono; Adhi Iswantoro; Ilham Rezandhi Akbar (International Journal of Marine Engineering Innovation and Research, 2020)
Piston is one of the important parts in the combustion process in a diesel engine, it consists of two namely the piston head and connecting rod, where the piston head consists of three parts, namely the piston crown, piston rings, and piston pins. This paper wants to prove which is more effective in modifying the TCC piston crown shape on a four-Stroke one-cylinder diesel engine fueled with B-30 in terms of noise. To measure noise, several experiments were carried out. One way is to use an application that can help make measurement easier is to use the simulation. The Simulation can measure the level of noise by using the tools in an application the same as in reality. The piston area is very influential on the combustion process, with the greater piston area, the resulting explosion is greater which results in and produces a high pressure also it is directly proportional to the noise level. After everything is measured, then we compare it with the engine's performance and give maximum results between the level of noise with engine performance. The result is using a piston case 4 (+1) which has a larger area experiencing the highest noise level using B30 Diesel Fuel or High-Speed Diesel (HSD) Fuel. Under load conditions, with a 50% load, the noise level on piston +1 (Case 4) experiences the highest noise level using B30 Diesel Fuel or High-Speed Diesel (HSD) Fuel.